The South China Sea: A breeding ground for geopolitical rivalry - Andreas Bøje Forsby (Danish Institute for International Studies (DIIS), 2016)
As an important commercial gateway and a rich source of natural resources, the South China Sea holds great economic and strategic significance. This is manifested not only in the conflicting territorial and maritime claims of the coastal states, but also in the simmering geopolitical rivalry between an increasingly self-assertive China and a United States bent on 'rebalancing' China's growing power in the region. This new DIIS report by Andreas Bøje Forsby examines recent development trends in the South China Sea, focusing primarily on three key areas: China's growing assertiveness in the South China Sea, the rebalancing efforts of the United States in the region and the recently-concluded arbitration case between the Philippines and China concerning their maritime dispute in the South China Sea. The report argues, firstly, that China's growing maritime assertiveness constitutes the main driver behind the heightened tensions and periodic clashes that have recently plagued the South China Sea. And secondly, that the US strategic rebalance in the region, notably the media-hyped freedom of navigation operations in the South China Sea, tends to exacerbate existing tensions, thus raising the specter of a comprehensive US-Chinese rivalry in the years to come. On the surface of it, the South China Sea may seem of limited interest from a Danish perspective. However, the report points out how the South China Sea disputes can undermine important aspects of a rule-based maritime order and ultimately force Denmark to choose sides if a full-fledged Sino-American rivalry materializes.
Keywords: 300